Ontogeny of lymphoid organs in the Asian sea bass (Lates calcarifer, Bloch) - Subburaj, R. (2021)
Ontogeny of the lymphoid organs of hatchery-reared larvae/juveniles Lates calcarifer (Bloch) was studied from zero day post hatch (dph) to 60 dph. Histological sections of the samples, collected at daily intervals from zero dph till 25 dph, and at weekly intervals till 60 dph were examined. The thymus was first noticed, at 2 dph, as a bi-lobed organ, situated dorso-posteriorly in the oro-pharyngeal cavity, in the angle between the opercular bone and the head bone. The lymphoid kidney (pronephros) was seen with undifferentiated stem cells at 2 dph, though the excretory kidney tubules were noticed at zero dph. The developed kidney runs ventral to the vertebral column all along the length of the peritoneal cavity, distinctly bi-lobed at its proximal end forming the head-kidney and fused in the mid and tail kidney portions. The spleen, seen mostly as an erythropoietic organ, is capsulated and appeared, at 2 dph, attached to the mesogastrium. The sequence of development of these lymphoid organs was: the thymus (2 dph), the kidney (excretory kidney-0 dph and lymphoid kidney -2dph), the spleen (2 dph) and the gut associated lymphoid tissue (GALT, 5 dph). Various cellular components of these lymphoid organs and their probable role in immune response of the fish have been discussed.